Trends in United States blood collection and transfusion: results from the 2013 AABB Blood Collection, Utilization, and Patient Blood Management Survey. Issue 9 (15th June 2016) - Whitaker, Barbee; Rajbhandary, Srijana; Kleinman, Steven; Harris, Andrea; Kamani, Naynesh
Abstract : BACKGROUND: AABB surveyed AABB institutional members about their 2013 blood collection, transfusion, and patient blood management (PBM) programs. Results were compared with previous US national surveys. STUDY DESIGN AND METHODS: The 2013 AABB Blood Collection, Utilization, and Patient Blood Management Survey was distributed to AABB blood centers (79) and hospitals (1068). Statistical procedures were used to estimate blood collection and transfusion. RESULTS: Estimated whole blood (WB) and red blood cell (RBC) collections in 2013 totaled 13.6 million units, a 12.1% decrease from 15.5 million units in 2011 (p < 0.0001). Transfusions of WB and RBC units by AABB hospitals totaled 6.1 million units, 7.3% fewer compared to 2011 (p = 0.036). There was no change in overall platelet (PLT) distributions by blood collectors but WB‐derived (WBD) PLT distributions increased significantly (27.1%, p < 0.0001). Transfusion of PLTs increased 15.4% totaling 1.3 million units (p = 0.0423), including increases in apheresis PLT (12.2%) and WBD PLT transfusions (30.7%). Distribution of plasma for transfusion declined 22.4% (p < 0.0001), while transfused plasma decreased only 9.9% (p = 0.036). Hospitals reduced outdated WB, RBC, and PLT components by 14.9% to 26.1% and wasted plasma components by 19.0%. PBM programs were reported by 37.8% of AABB hospitals. CONCLUSIONS: Compared to 2011, WB and RBC collections declined significantly in 2013 and disproportionately to the significant reductions in WB and RBC transfusions. Distributions of PLTs and plasma for transfusion declined in 2013, as did transfusions of plasma, while transfusion of PLTs increased significantly. Decreases in outdated and wasted components by hospitals suggest improvements in product and inventory management. Ongoing national surveys allow for trend analysis and are important for future planning.